2018
DOI: 10.1186/s13075-018-1784-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to health-related quality of life in ankylosing spondylitis, overall and stratified by sex

Abstract: BackgroundAnkylosing spondylitis (AS) begins early in life and often leads to reduced physical function, but less is known about the impacts it has on health-related quality of life (HRQoL). The aims of this study were to assess HRQoL using the Short Form-36 (SF-36) in a cohort of patients with AS compared with controls and to examine associations between SF-36 scores and spinal radiographic changes, physical function, disease activity and demographic data overall and stratified by sex.MethodsA cohort of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
(56 reference statements)
3
48
0
9
Order By: Relevance
“…Therefore, based on both results, the second hypothesis, that the level of anxiety and pain would increase at the first tube replacement, compared to the levels of pain and anxiety presented before implantation, was not confirmed. These result coincides with other studies ( 35 - 38 ) . Regarding the gender difference in anxiety, other articles ( 39 ) suggest that there may be factors intrinsic to the female gender that predispose them to present more comorbidities, such as biochemical, hormonal and/or social aspects, that explain the differences per genus.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, based on both results, the second hypothesis, that the level of anxiety and pain would increase at the first tube replacement, compared to the levels of pain and anxiety presented before implantation, was not confirmed. These result coincides with other studies ( 35 - 38 ) . Regarding the gender difference in anxiety, other articles ( 39 ) suggest that there may be factors intrinsic to the female gender that predispose them to present more comorbidities, such as biochemical, hormonal and/or social aspects, that explain the differences per genus.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that patients with ax-SpA report HRQOL scores that are similar to those reported for other inflammatory diseases [2,10], but lower than those in healthy controls [1,4,[11][12][13]. Women with the ax-SpA report lower HRQOL than men [14][15][16], and decreased HRQOL in patients with ax-SpA is associated with fatigue [17], increased disease activity, decreased daily activity and exercise [4,[18][19][20], pain, and adverse psychological factors such as body-image disturbance, anxiety and depression [21,22].…”
mentioning
confidence: 62%
“…Spearman correlation coefficients were calculated to assess the correlation between ASAS HI and PROs. Candidate variables for regression analysis were referred to the previous studies which investigated associated factors of HRQoL and structural progression in SpA [16,17]. Linear regression analysis was performed to determine predictors of ASAS HI.…”
Section: Methodsmentioning
confidence: 99%